An in vitro study on the antimicrobial property of hierba buena - Angeles, Jocelyn I.
This in vitro study intends to determine the antimicrobial activity of hierba buena against some common microorganisms found in the oral cavity, and its appropriate form a preparation to be used. Hierba buena extracts in different concentrations ranging from the 10% to 200% were used. Afterwhich, the extracts were subjected to filter paper anaerobic microorganisms. Analysis of the results shows that hierba buena has an antimicrobial effect in S. aureus, BH Streptoccoccus, A. Albicans, Bacteroides, and Lactobacillus at various concentrations through decoction.